DI-014 Off label use and economic impact of biologic therapy in non-infectious uveitis. (24th March 2015) - Manzaneque, A; Sotoca, JM; Rivero, A; Camos, A; Matas, J; Adán, A; Codina, C
Abstract : Background: Non-infectious uveitis represents a heterogeneous group of inflammatory intraocular diseases. Conventional treatment with corticosteroids and immunosuppressive agents may not be sufficient in refractory patients. Off-label use of biological response modifiers has been studied as an alternative. Purpose: To describe the use and financial impact of biological treatment in refractory non-infectious uveitis. Material and methods: Retrospective, observational study. We included patients with non-infectious uveitis treated with biological agents between 2009 and June 2014. Patients were identified by reviewing off-label uveitis authorizations and data was collected from electronic medical records. Individual costs were calculated using the hospital acquisition prices. Results: 79 patients (117 biologicals) were identified: 75% women, 41 ± 16 years old. Anatomic diagnosis was: posterior (46.8%), anterior (32.9%), panuveitis (13.9%) and intermediate (6.3%) uveitis. Of the biological agents prescribed to the 85.5% of patients with anti-TNF (14.5% tocilizumab), the most prescribed was adalimumab (55%), followed by infliximab (33%), golimumab (9%) and certolizumab (3%). Over 80% of patients received one drug, 10% two, 9% three and only one patient received four. The main reason for switching was: loss of efficacy (18.2% infliximab, 44.4% golimumab, 33% certolizumab, 11.8% infliximab) and side effects (9.1% adalimumab, 11.8% tocilizumab). 23.1% of anti-TNF and 20% of tocilizumab could be discontinued for stable disease. In the financial analysis (n = 54), overall cost/patient varied from €2, 030 to 98, 250 (median €12, 940). The cost associated with each drug was: €23, 430, €21, 100, €12, 320, €3, 960, and €21, 025; with a mean duration of 15.4, 18.6, 13.6, 4.9, and 11.3 months, until the final follow-up date, for infliximab, adalimumab, golimumab, certolizumab and tocilizumab respectively. Conclusion: TNF blockers and tocilizumab may benefit patients when conventional immunosuppressive treatment has failed or has been poorly tolerated. Given their cost as well as the lack of studies related to effectiveness and long-term safety, they cannot be used routinely. Reference: Pasadhika S, Rosenbaum JT. Biologics 2014;8:67–81 No conflict of interest.